A combination of additives can synergically decrease acrylamide content in gingerbread without compromising sensory quality - Komprda, Tomáš; Pridal, Antonin; Mikulíková, Renata; Svoboda, Zdeněk; Cwiková, Olga; Nedomová, Šárka; Sýkora, Vladimír (Journal of the Science of Food and Agriculture, 2017)
BACKGROUND: The present study tested whether replacement of the leavening agent ammonium carbonate by sodium hydrogen carbonate in combination with calcium cation and acidifying agent will synergically decrease acrylamide (AA) content in gingerbread. RESULTS: The type of leavening agent and the presence of Ca(2+) and citric acid accounted for 33.6%, 13.2% and 53.2% of the explained variability of the AA content, respectively (P < 0.01). The AA content in gingerbread produced with (NH4 )2 CO3 alone was 186.5 µg kg(-1) . Irrespective of other tested additives, NaHCO3 decreased (P < 0.05) AA content to 42% compared to (NH4 )2 CO3 . Combination of NaHCO3 + CaCl2 + citric acid in dough reduced (P < 0.05) AA content below the limit of detection (25 µg kg(-1) ). The AA content in gingerbread (y; µg kg(-1) ) decreased with an increasing number of additives used (x) according to the equation y = 158.8 - 47.94x (r(2) = 0.42; P < 0.0001). A comprehensive sensory analysis did not indicate any significant deterioration (P > 0.05) in the organoleptic quality of gingerbread produced using calcium cation and citric acid. CONCLUSION: The present study demonstrates that the combination of additives NaHCO3 /Ca(2+) /citric acid synergically decreases AA content in gingerbread without compromising the sensory quality. © 2016 Society of Chemical Industry.
Keywords: Citric Acid; kontaminace potravin; akrylamid; Consumer Behavior; chemické jevy; Mechanical Phenomena; Sodium Bicarbonate; čití, cítění; lidé; kyselina citronová; Maillardova reakce; Food Quality; vaření; Fast Foods; Food Contamination; Czech Republic; Česká republika; chování spotřebitelů; Hydrogen-Ion Concentration; Calcium Chloride; Maillard Reaction; kvalita jídla; mechanické jevy; preference v jídle; koncentrace vodíkových iontů; průmyslově zpracované potraviny; Acrylamide; Food Additives; algoritmy; uhličitany; hydrogenuhličitan sodný; Carbonates; Chemical Phenomena; Cooking; potravinářské přísady; Humans; Algorithms; Food Preferences; chlorid vápenatý; Sensation